Fundamentals of HIV medicine 2019 - Hardy, W. David (William David), 1955-; American Academy of HIV Medicine (New York, NY : Oxford University Press, 2020)
The essential work in HIV for providers and pharmacists - updated with everything they need to know in 2019. Assembled by the leading educational organization in HIV medicine, this title is an end-to-end clinical resource for the treatment of individuals with HIV/AIDS. It offers state-of-the-art practical advice for physicians, pharmacists, nurse practitioners, and other professionals working in the care of HIV patients.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 26, 2020).
Keywords: HIV infections